Studi Kelayakan Pemanfaatan PV sebagai Sumber Energi Ruang Pendingin Karkas Ayam Broiler - Efendi, Mutiara; Hamzah, Reodhy; Indah Negara, Vamellia Sari; Araliz, Maheka Restu (Politeknik Negeri Padang, 2024)
When chicken prices drop, farmers often extend the harvesting period, which inevitably increases production costs. An alternative solution is to store chickens as carcasses in cooling storage. Indonesia has significant solar energy potential for the implementation of solar cooling storage technology to reduce electricity costs as a power source for cooling storage. This study aimed to analyze the economic feasibility of designing solar cooling storage with a one-ton carcass capacity. The research method involved analyzing the costs of implementing cooling storage by comparing the costs of electricity sourced from PLN, solar energy using PV, and extending the harvesting period by up to 10 days. The analysis results showed that the designed cooling storage had a capacity of 12 m³, and the production costs for storing carcasses using hybrid PLN and PV electricity were more efficient than using PLN electricity alone. This cost-saving approach is significantly more efficient than the production costs incurred when farmers extended the harvesting period. In terms of economic feasibility, the BEP values for PLN and PV electricity sources were 18.86 and 21.02 years, respectively. The calculations showed a BEP difference of approximately 5 years between PLN and PV electricity; however, economically, PV systems were more advantageous in the long term.